Communes et omnibus notas. Sulla relazione tra litterae communes e rudimenta litterarum fra età tardoantica e precarolingia - Boccuzzi, Maria (Scrineum, 2021)
This paper focuses on the interrelated meanings of the expression litterae communes as attested in different types of sources. One group of texts includes a law issued by the emperors Valentinian and Valens and one of the Justinian’s novels; here litterae communes is employed to refer to the minuscule writing system of the new Roman cursive, which was widespread in documentary practices outside the imperial chancery and, more generally, in current uses since the 4th century onwards. Another type of sources comprises pedagogical-grammatical texts from Late Antiquity to early Middle Ages, where the expression litterae communes relates to the rudimenta litterarum that could be learnt through primary education. The convergence point between these seemingly different meanings lies in the letterforms used for teaching/learning writing, as revealed by the comparison between the graphic models at the basis of elementary writings and the scripts employed for pragmatic purposes from Late Antiquity to Precarolingian Age.